Implementasi Media Pembelajaran Edpuzzel Dalam Meningkatkan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Aqidah Akhlak - Suriyati, Suriyati; Bahrum, St. Rahmaniah; P, Sudirman; Jamaluddin, Jamaluddin; Rahmatullah, Rahmatullah; Sari, Nurfika Indah (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study aims to determine whether there is an increase in students' learning motivation after being given treatment using edpuzzel learning media. The type of research is quantitative with an experimental approach. The subjects of the study were grade VIII students. The data collection techniques were observation, questionnaires and documentation. The data analysis technique was statistical testing. The results of the study showed that edpuzzel learning media can increase students' learning motivation. The results of the analysis carried out by researchers using the SPSS version 25 application by comparing the pretest and posttest values ​​obtained a mean value of the pre-test of 84.65, a maximum value of 88.00, and a minimum value of 76.0. While the post-test value can be obtained a mean value of 89.45, a maximum value of 97.00 and a minimum value of 82.00. The pre-test and post-test values ​​above show that there is a significant difference between before and after being given treatment using edpuzzel learning media in the subject of aqidah akhlak. In addition, the value of the t-test results, obtained a sig value = 0.000, which means it is smaller than α 0.05. Thus, Ho is rejected and Ha is accepted.